2017
DOI: 10.1111/phen.12186
|View full text |Cite
|
Sign up to set email alerts
|

The more, the merrier? Obligate symbiont density changes over time under controlled environmental conditions, yet holds no clear fitness consequences

Abstract: Symbiotic bacteria are highly diverse, play an important role in ecology and evolution, and are also of applied relevance because many pest insects rely on them for their success. However, the dynamics and regulation of symbiotic bacteria within hosts is complex and still poorly understood outside of a few model systems. One of the most intriguing symbiotic relationships is the obligate, tripartite nutritional mutualism in sap‐feeding, economically‐destructive mealybugs (Hemiptera: Sternorrhyncha: Pseudococcid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 73 publications
(87 reference statements)
2
12
0
Order By: Relevance
“…The density of the primary symbiont, Buchnera , in pea aphids tends to decrease with host age and increase with rearing temperature (Lu, Chiu, & Kuo, ). In this study, bacterial density variation was prospected in the natural adult A. gossypii population; the results showed the flexible dynamics of bacterial density over time, although the higher levels of symbionts have no clear benefit to the hosts and therefore appeared to be superfluous (Parkinson et al., ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The density of the primary symbiont, Buchnera , in pea aphids tends to decrease with host age and increase with rearing temperature (Lu, Chiu, & Kuo, ). In this study, bacterial density variation was prospected in the natural adult A. gossypii population; the results showed the flexible dynamics of bacterial density over time, although the higher levels of symbionts have no clear benefit to the hosts and therefore appeared to be superfluous (Parkinson et al., ).…”
Section: Discussionmentioning
confidence: 87%
“…Environmental factors influenced the symbiont density and composition in normal plots, while both were changed depending on the sampled day. Symbiont density is found to differ significantly between the populations when reared under controlled environmental conditions in mealy bugs (Parkinson, Gobin, & Hughes, ). The density of the primary symbiont, Buchnera , in pea aphids tends to decrease with host age and increase with rearing temperature (Lu, Chiu, & Kuo, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is so important to host fitness, many hosts have evolved unique strategies to manipulate symbiont or partner abundance to their own advantage (Cunning et al, 2015;Parkinson, Gobin, & Hughes, 2016;Parkinson et al, 2017). For example, crayfish hosts (Cambaridae: Cambarus chasmodactylus and Orconectes cristavarius) actively reduce density of branchiobdellidan worms to prevent a mutualistic cleaning symbiosis from switching to parasitism (Farrell, Creed, & Brown, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As is the case for aphids and carpenter ants, mealybug obligate symbionts are hypothesized to primarily control gene expression by altering symbiont density within the host (Kono et al ., ). However, a recent study found that laboratory populations of the citrus mealybug under identical environmental conditions differed from each other in their symbiont density, with this density being heritable, although there were no clear fitness benefits or costs associated with higher obligate symbiont density in terms of development, growth or fecundity (Parkinson et al ., , , ).…”
Section: Introductionmentioning
confidence: 99%